Rose tea for lowering blood pressure and alleviating stress: Sensory analysis and in silico investigations - Igoy Bimo (22676155) (2025)
Rose tea has attracted increasing interest for its distinctive sensory properties and potential health benefits, yet the scientific evidence connecting these aspects remains limited. This study examined rose tea from Batu, East Java, through an integrated approach combining sensory evaluation, chemical profiling, physiological stress assessment, and in silico analysis. Sensory evaluation was conducted with forty-three healthy untrained panelists aged 20–24 years, using a 5-point hedonic scale and the rate-all-that-apply method to assess taste, aroma, and color. Water served as the negative control and L-theanine as the positive control. Among the samples evaluated, the preparation dried at 80 °C for 3 hours received the highest preference scores, noted for its floral aroma, balanced taste, and appealing coloration. Chemical analysis of this preferred sample identified phenolics, flavonoids, and key volatiles such as benzeneacetaldehyde, nonanal, and n-hexadecanoic acid, several of which are associated with both sensory attributes and biological activity. Molecular docking suggested that these compounds may interact selectively with the angiotensin-converting enzyme C-domain and with targets related to stress modulation. Short-term physiological assessments supported these findings, showing reductions in heart rate and perceived stress comparable to those induced by L-theanine. These results indicate that the same compounds contributing to consumer-preferred sensory characteristics may also underpin the functional properties of rose tea. Nevertheless, the study is limited by its focus on a narrow demographic, reliance on short-term and computational measures, and the absence of clinical validation. Broader and longer-term studies are required to substantiate the efficacy of rose tea as a nutraceutical beverage.